Analisis Kesalahan Berbahasa Pada Teks Deskripsi dalam Tataran Linguistik di MTS Bahrul Ulum Kelas VII - Dwi Rinna Artiani; Gina Amelia; Muhamad Alqodri Ali Herdiana; Ai Siti Nurjamilah (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
This research aims to describe in detail the analysis of language errors in descriptive texts at the linguistic level which includes errors in phonology, morphology, syntax, semantics, spelling and punctuation. The method used in this research is a descriptive qualitative method. The data from this research are text descriptions of the work of 30 class VII MTS Bahrul Ulum students, and 5 texts were used as samples in this research. The data collection technique in this research was obtained by requesting data from the school through the teacher concerned. The object of this research is the results of student assignments in the form of descriptive text and then the data obtained is analyzed. Data analysis was carried out by reading, analyzing and classifying the data, then the results of the language error analysis were depicted in tables and conclusions were described. The results of the research show that language errors in the descriptive texts of class VII students at MTS Bahrul Ulum include: 1) Phonology with 7 errors, consisting of phoneme changes and phoneme deletions, 2) Morphology with 4 errors consisting of reduplication, composition and affixation errors, 3) 2 semantic errors consist of the use of non-standard words and unclear meanings, 4) 14 spelling errors consist of errors in the use of capital letters and punctuation errors. 4 times, consisting of errors in placing commas, spaces and periods. Based on the results of this research, researchers hope that it can be used as a reference and feedback for both students who are learners, and more specifically for educators, language users, or even for other researchers.